RISK MANAGEMENT, COMPANY RISK, MODERATING ROLE OF BOARD GENDER DIVERSITY - Johanes Felix Gunawan; Rio Christantio Hakim; Riki Martusa; Meythi Meythi (Jurnal Bisnis dan Akuntansi, 2025)
The research has intention to observe the impact of corporate board risk management on the risks faced by the company moderated by board gender diversity in non-financial corporations indexed on the Indonesian stock index during 2023. This research sample consist of 704 non-financial corporations indexed on the Indonesian stock exchange during 2023 and issued 2023 annual reports. This research finding that management of risk conducted by the board negatively affects the risks faced by the company. Gender diversity moderates this relationship with mixed results where the presence of women has positive result while moderate the relationship between risk management and firm risk while gender diversity in corporations board has negative result while moderates the relationship betwixt risk management and firm risk. Contribution of this study is to enrich the literature related to risk management and gender diversity in corporation board in the Indonesian context and provides an overview of the impacts of implementing policies to promote diversity in gender in Indonesian companies